Advancing immune checkpoint blockade in colorectal cancer therapy with nanotechnology - Liu, Zefan; Xiang, Yucheng; Zheng, Yaxian; Kang, Xin (Frontiers in Immunology, 2022)
Immune checkpoint blockade (ICB) has gained unparalleled success in the treatment of colorectal cancer (CRC). However, undesired side effects, unsatisfactory response rates, tumor metastasis, and drug resistance still hinder the further application of ICB therapy against CRC. Advancing ICB with nanotechnology can be game-changing. With the development of immuno-oncology and nanomaterials, various nanoplatforms have been fabricated to enhance the efficacy of ICB in CRC treatment. Herein, this review systematically summarizes these recent nano-strategies according to their mechanisms. Despite their diverse and complex designs, these nanoplatforms have four main mechanisms in enhancing ICB: 1) targeting immune checkpoint inhibitors (ICIs) to tumor foci, 2) increasing tumor immunogenicity, 3) remodeling tumor microenvironment, and 4) pre-sensitizing immune systems. Importantly, advantages of nanotechnology in CRC, such as innovating the mode-of-actions of ICB, modulating intestinal microbiome, and integrating the whole process of antigen presentation, are highlighted in this review. In general, this review describes the latest application of nanotechnology for CRC immunotherapy in the aspect of drug-material-organism interactions, and may shed light on the future design of ICB platforms.